1988
DOI: 10.1002/1097-0355(198822)9:2<173::aid-imhj2280090205>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' and fathers' speech to infants in a teaching situation

Abstract: The purpose of this study was to compare mothers' and fathers' speech to their preverbal infants in a teaching situation. Thirty‐two parents of 16 8‐month‐olds were asked to teach their infants to put a small cube into a cup. Infant Gender (2) x Birth Order (2) x Parent (2) analyses of variance were performed with repeated measures on parent. Results indicated that fathers issued more utterances and used more words per utterance than did mothers. Although there was no difference in the proportion of imperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…Other studies report further functional differences. For instance, Brachfeld‐Child and colleagues (1988) observed mothers to use more negative statements, imperatives, and exhortations to daughters than to sons. Fathers have been observed to adapt their style more to the child's gender, especially concerning negative responses to daughters (Kerig et al.…”
Section: Gender In Child‐directed Speech and In Child Discoursementioning
confidence: 99%
See 1 more Smart Citation
“…Other studies report further functional differences. For instance, Brachfeld‐Child and colleagues (1988) observed mothers to use more negative statements, imperatives, and exhortations to daughters than to sons. Fathers have been observed to adapt their style more to the child's gender, especially concerning negative responses to daughters (Kerig et al.…”
Section: Gender In Child‐directed Speech and In Child Discoursementioning
confidence: 99%
“…Fathers’ speech is often characterized as a more ‘directive’ style (Malone & Guy 1982; Andrews & Ratner 1987). Brachfeld‐Child et al. (1988) report some child as well as parental gender differences: addressing 18 month old infants, fathers’ imperatives were significantly longer than mothers’, mothers tended to use more exact repetitions, and parents directed more utterances, particularly negative statements, imperatives, and exhortations, to girls than to boys.…”
Section: Gender In Child‐directed Speech and In Child Discoursementioning
confidence: 99%
“…Differences between fathers and mothers in the style and amount of talk to children are well-documented (e.g., Pine 1994;Snow 1995). Brachfeld-Child, Simpson and Izenson (1988) reported that fathers make greater efforts than mothers to control the situation and to direct their children's behavior. Thus, we may speculate that the different distributions of types of affect words in our parental speech data may reflect the different speech styles used by fathers and mothers to socialize children's affect and their behavior.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also evidence that fathers’ language use may be beneficial to children's language learning in ways that differ from mothers. For example, fathers have been shown to use a greater number of different and uncommon words than mothers (Masur & Gleason, 1980; Ratner, 1988), request more object labels from their children (Masur & Gleason, 1980) and use more extensive vocabulary when it is specifically relevant to a task (Brachfeld-Child, Simpson, & Izenson, 1988). Some theories suggest that this arguably more demanding use of language functions to extend and broaden children's language (i.e., “bridge hypothesis”; Gleason, 1975).…”
Section: Mothers and Fathersmentioning
confidence: 99%